ANALISIS KEANDALAN SISTEM JARINGAN DISTRIBUSI 20 KV PENYULANG BP1 DI PT.PLN (PERSERO) UP3 GORONTALO DENGAN METODE SECTION TECHNIQUE - Polingala, Reynaldi; Harun, Ervan Hasan; Yusuf, Taufik Ismail (Journal Of Renewable Energy Engineering, 2025)
One of the important factors and main indicators of the quality of electricity supply services from the system to customers is the reliability of the distribution network. Frequent disruptions to the distribution network can reduce the reliability of electricity distribution. Based on data obtained from PLN UP3 Gorontalo, the BP1 feeder is a vulnerable area that experiences the most frequent service disruptions, with a total of 96 disruptions during 2023. This study aims to determine the reliability index value of the 20 kV distribution system for the BP1 feeder using the section technique, and to determine the undistributed energy and the losses incurred due to blackouts in the BP1 feeder. The method used in this study is the section technique, which evaluates a distribution system by assessing how the failure of a piece of equipment affects its operation. The results of the study show that the reliability index for the BP1 feeder in 2023 is SAIFI of 15.43 times/customer/year, SAIDI of 3.61 hours/customer/year, and CAIDI of 0.23 hours/customer. From these results, it can be concluded that the SAIFI value for the BP1 feeder is not yet reliable, as it does not meet the SPLN 68-2:1986 standard of 3.2 times/year. Meanwhile, the SAIDI value of the BP1 feeder is reliable because it meets the SPLN 68-2:1986 standard value of 21.09 hours/year. The unsupplied energy (ENS) is 18,809.81 kWh, so the loss value for the BP1 feeder in 2023 is Rp. 30,933,106.55.